PEMBENTUKAN ELECTRONIC WORD OF MOUTH POSITIF MELALUI LAMAN INSTAGRAM STUDI PADA KONSUMEN FATAHILLAH GINTING PHOTOGRAPHY - Nufy Gera Rahmadany Sembiring; Zuwina Miraza (Jurnal Manajemen Bisnis Eka Prasetya, 2019)
The growth of internet users in Indonesia continues to increase. Hence, many companies ranging from micro, small, medium to large businesses, utilize Instagram in increasing their sales through electronic word of mouth processes. This study aims to determine the influence of perceived quality, experiential marketing on customer satisfaction and eWOM on Instagram. Population of this study are the clients who have used the services of Fatahillah Ginting Photography. The data collected from 170 respondents using questionnaire, and analyzed by path analysis technique. Some tests were conducted in this research are data quality test, classical assumption test, conformity test and path analysis. The Result shows that Perception of Quality and Experiential Marketing have direct influence on eWOM and indirectly through Consumer Satisfaction. Thus, in order to create positive eWOM on Instagram, Fatahillah Ginting Photography needs to increase customer loyalty by implementing experiential marketing concepts and providing high quality services.